Ethnobotany of Minangkabau Culinary and Their Phytochemical Test - Agesti, Asih Rahayu Ajeng; Fitmawati, Fitmawati; Dianti, Putri Rahma; Al Yamini, Thobib Hasan (Jurnal Biologi Tropis, 2025)
Minangkabau ethnic has rich natural and cultural resources. The Minangkabau ethnic community in Lima Puluh Kota Regency, West Sumatra, possesses rich traditional knowledge in utilizing local plant species as ingredients in their culinary heritage. This study aimed to document the ethnobotanical use of food plants and examine their phytochemical properties to assess their potential as functional foods. Ethnobotanical data were collected using open-ended interviews and field observations involving key informants from various Nagari (villages) selected using purposive sampling methods. Phytochemical tests were conducted to identify alkaloids, saponins, steroids, tannins, and triterpenoids in the plants used. The study identified 43 plant species belonging to 29 families used as the main ingredients in 20 types of traditional culinary with plant species are dominated by Fabaceae. Leaves were the most frequently used plant parts, followed by fruits, stems, flowers, and tubers. These ingredients were sourced from wild and cultivated plants growing in yards, gardens, and fields. Phytochemical screening of  plants revealed the presence of secondary metabolites including alkaloids (13 species), flavonoids (26), saponins (21), tannins (21), triterpenoids (16), and steroids (8). The findings of our study indicate that traditional Minangkabau food plants are not only culturally significant but also possess medicinal potential, warranting further scientific exploration and conservation of local knowledge.